Non-Invasive Brain Stimulation: An Interventional Tool for Enhancing Behavioral Training after Stroke - Wessel, Maximilian J.; Zimerman, Máximo; Hummel, Friedhelm C. (Frontiers in Human Neuroscience, 2015)
Stroke is the leading cause of disability among adults. Motor deficit is the most common impairment after stroke. Especially, deficits in fine motor skills impair numerous activities of daily life. Re-acquisition of motor skills resulting in improved or more accurate motor performance is paramount to regain function, and is the basis of behavioral motor therapy after stroke. Within the past years, there has been a rapid technological and methodological development in neuroimaging leading to a significant progress in the understanding of the neural substrates that underlie motor skill acquisition and functional recovery in stroke patients. Based on this and the development of novel non-invasive brain stimulation techniques, new adjuvant interventional approaches that augment the response to behavioral training have been proposed. Transcranial direct current (tDCS), transcranial magnetic (TMS) and paired associative (PAS) stimulation are noninvasive brain stimulation techniques that can modulate cortical excitability, neuronal plasticity and interact with learning and memory in both healthy individuals and stroke patients. These techniques can enhance the effect of practice and facilitate the retention of tasks that mimic daily life activities. The purpose of the present review is to provide a comprehensive overview of neuroplastic phenomena in the motor system during learning of a motor skill, recovery after brain injury, and of interventional strategies to enhance the beneficial effects of customarily used neurorehabilitation after stroke.